A case report of infantile fibrosarcoma with BRAF gene mutation with incomplete intestinal obstruction - Zhu, Fan; Fan, Liang; Cui, Guanhua; Jian, Hai; Zhou, Hongjie; Xu, Jianfeng; Chen, Fengshun (Frontiers in Oncology, 2025)
ObjectiveThis study aims to explore the clinical features, diagnosis, and treatment of infantile fibrosarcoma (IFS) associated with BRAF mutations, with the goal of enhancing clinicians’ understanding of this rare genetic variant and its relationship to IFS.MethodsThe China National Knowledge Infrastructure (CNKI), Wanfang Database, VIP Database, PubMed, and National Center for Biotechnology Information (NCBI) were searched using the keywords “infantile fibrosarcoma” and “congenital fibrosarcoma” for relevant articles published before August 2024. A total of 529 articles and 498 cases were identified, of which 48 articles and 149 cases were in Chinese and 479 articles and 349 cases were in foreign languages. Among them, 20 cases occurred in the gastrointestinal tract, with two cases associated with BRAF gene mutation. Combining the case reported in this paper, the clinical manifestations and treatment experience were summarized.ResultsThe patient was a male infant aged 5 months 18 days who presented with vomiting for 4 days. Preoperative abdominal ultrasonography revealed an abnormal hyper-echoic mass in the right upper abdomen. Exploratory laparotomy and complete tumor excision were performed. Pathological examination confirmed a diagnosis of IFS, with molecular analysis identifying a BRAF p.V600delinsDL mutation. Postoperative follow-up over 8 months showed no recurrence or metastasis on abdominal ultrasound. A review of this case alongside 20 reported cases of intestinal IFS revealed that intestinal perforation and obstruction were the most common presentations, with favorable overall prognoses.ConclusionIntestinal IFS is a rare soft tissue sarcoma predominantly occurring in early infancy. Cases involving the BRAF p.V600delinsDL mutation are even rarer. Treatment should be individualized, with complete surgical resection being the cornerstone of therapy. Prognosis remains favorable following complete excision.